Síntese e determinação da estrutura cristalina de um novo semicondutor molecular com aminoantraquinona (AAQ) e tetracianoquinodimetano (TCNQ) e uma contribuição à química de coordenação do TCNQ com cobre (II) em THF - Santos, Jaciara Nascimento (2013)
The reaction of 1-aminoanthraquinone with 7,7,8,8-tetracyanoquinodimethane in dichloromethane yielded the charge-transfer complex with semiconducting characteristics, C14H9NO2·C12H4N4. The molecules have maximum deviations from the mean planes through the non-H atoms of 0.0769 (14) Å for an oxo O atom and 0.1175 (17) Å for a cyano N atom, respectively. The dihedral angle between the two planes is 3.55 (3)°. In the crystal, molecules are stacked into columns along the a-axis direction. Pairs of N-H...N and N-H...O interactions connect the molecules perpendicular to the stacking direction. Additionally, an intramolecular N-H O hydrogen-bond interaction is observed for 1-aminoanthraquinone. A charge transfer is present, since the electrical resistivity falls with increasing temperature indicating semiconducting characteristics. From the resistivity data, an Arrhenius development ln(1/R) versus 1/T gives a mainly linear behaviour, from which a small barrier for the thermally activated transport of 1.25 eV can be derived. Dark brown crystals, suitable for X-ray analysis, were obtained by the slow evaporation of the solvent. Elemental analysis: Calc. 73.1 C, 3.1 H, 16.4 N; found 72.8 C, 3.4 H, 16.6 N. The melting point was determined by differential scanning calorimetry to 520 K. Exothermic decomposition occurs at 555 K. This work is already published (Oliveira et al., Acta Cryst. (2013). E69, o301). The coordination chemistry of tetracyanoquinodimethane was investigated with a reaction with Cu (II) in tetrahydrofurane. The results were analyzed with infrared, thermal analysis and cyclic voltammetry data and showed the coordination through the cyano groups of tetracyanoquinodimethane and the metal center.